Year in Review: Synopsis of Selected Articles in Neuroanesthesia and Neurocritical Care from 2019 - Leong, KokWeng; Dalby, Tara; Venkatraghavan, Lashmi (Journal of Neuroanaesthesiology and Critical Care, 2020)
This review is a synopsis of selected articles from neuroscience, neuroanesthesia, and neurocritical care from 2019 (January–November 2019). The journals reviewed included anesthesia journals, critical care medicine journals, neurosurgical journals, as well as high-impact medical journals such as the Lancet, Journal of American Medical Association, New England Journal of Medicine, and Stroke. This summary of important articles will serve to update the knowledge of anesthesiologists and other perioperative physicians who provide care to neurosurgical and neurocritical cases.
Keywords: key articles; neurocritical care; neurosurgery